Mechanism of antifungal activity of virgin coconut oil on cell membrane of Candida Albicans - Mukhtar, Nor Izzah; Abllah, Zurainie; Mohamad, Mohd Azrul Naim; Shahdan, Intan Azura; Haron, Ummi Aqilah (Ektodermal Displazi Grubu, 2020)
Oral candidiasis is typically caused by diploid yeast, Candida albicans through the colonization of the yeast. Which may cause oral tissue damage and tissue invasion. The limitation of antifungal drugs such as problem with resistance development has led researchers to investigate the potential use of natural product as new target for antifungal drug development. The aim of this study is to identify the components cytoplasmic release and the morphology of C. albicans in the presence of activated virgin coconut oil (AVCO) and the crude extract of virgin coconut oil (VCO). The fungal suspensions were treated with AVCO and VCO while nystatin and 1% Tween were used as a positive and a negative control respectively. Treatment with AVCO has caused disruption of the cell membrane of C. albicans which leads to the leakage of the cytoplasmic contents while treatment with VCO which did not show any changes on the cell membrane of C. albicans after 4 h of exposure. Our results suggest the potential use of AVCO as a novel antifungal agent to control oral candidiasis and it is likely to become an alternative for conventional drugs available in the market.